Never the same after the first time: the satisfaction of the second-generation self-employed - Andrew E. Clark; Nathalie Colombier; David Masclet (Institute for the Study of Labor (IZA), 2008)
Previous empirical work has shown that the self-employed are generally more satisfied than salaried workers. This paper contributes to the existing literature in two ways. First, using French data from the ECHP and British data from the BHPS, we investigate the domains over which this differential operates. We show that, after controlling for occupation, self-employed workers are generally more satisfied with working conditions and pay, but less satisfied than employees with respect to job security. We then consider the differences between the first- and second-generation self-employed. The first-generation self-employed (those whose parents were not self-employed) are more satisfied overall than are the second-generation self-employed. We argue that this finding is consistent with the self-employed partly comparing their labor market outcomes with those of their parents, as well as parental transfers which loosen the self-employment participation constraint. This result is found in both pooled and panel analysis.
urn:nbn:de:101:1-2008050224
Keywords: J20; 330; Satisfaction; self-employment; parents; intergenerational comparisons; Selbstständige; Generationenbeziehungen; Arbeitszufriedenheit; Lebenszufriedenheit; Frankreich; Großbritannien